2012
DOI: 10.3109/01443615.2011.637140
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of obstetric complications in Kassala Hospital, Eastern Sudan

Abstract: Medical files of women delivered at Kassala Hospital, Eastern Sudan in the period of January-December 2009 were reviewed retrospectively. Out of 4,689 delivered women, 14.7% were teenagers, 67.1% had no antenatal care and 12.6% were grandmultiparous. Obstetric complications included: pre-term birth (2.6%); pre-eclampsia/eclampsia (4.2%); haemorrhage (2.9%); malpresentation (5.5%); obstructed labour (1.9%) and ruptured uterus (0.6%). Caesarean delivery rate was 31.1%. While 89.4% of the newborn babies were take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 11 publications
0
38
0
Order By: Relevance
“…Pre-eclamsia is a multisystem disorder that complicates 3% -8% of pregnancies in western countries and constitutes a major source of morbidity and mortality worldwide [19] [20]. While in Sudan the complication with pre-eclampsia/eclampsia is 4.2% [21]. The current study aimed to estimate and evaluation of the plasma D-dimer level in Sudanese preeclampsia women.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-eclamsia is a multisystem disorder that complicates 3% -8% of pregnancies in western countries and constitutes a major source of morbidity and mortality worldwide [19] [20]. While in Sudan the complication with pre-eclampsia/eclampsia is 4.2% [21]. The current study aimed to estimate and evaluation of the plasma D-dimer level in Sudanese preeclampsia women.…”
Section: Discussionmentioning
confidence: 99%
“…calcium and zinc supplement [18]. In Sudan, preeclampsia/eclampsia is a major cause of maternal and perinatal morbidity and mortality [1, 19, 20]. We have previously shown that preeclampsia is associated with oxidative stress [21].…”
Section: Introductionmentioning
confidence: 99%
“…There is an extremely high maternal mortality in Sudan where preeclampsia/eclampsia is the main cause of obstetric complications and maternal deaths (17, 18). In Sudan, several aspects of preeclampsia were investigated (1923); however, there were no published data on thyroid function/antibodies in preeclamptic patients.…”
Section: Introductionmentioning
confidence: 99%